2011
DOI: 10.1007/978-3-642-23318-0_5
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Performance of Recommender Systems: An Information Theoretic Approach

Abstract: Esta es la versión de autor de la comunicación de congreso publicada en: This is an author produced version of a paper published in: Abstract. Performance prediction is an appealing problem in Recommender Systems, as it enables an array of strategies for deciding when to deliver or hold back recommendations based on their foreseen accuracy. The problem, however, has been barely addressed explicitly in the area. In this paper, we propose adaptations of query clarity techniques from ad-hoc Information Retrieval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…genres. Although other measures could be available where no external information is required, such as the entropy of the ratings [12] or the Kullback-Leibler divergence between the user's preferences and the overall preferences [4], we believe that our formulation provides a measure that is easily explainable and justifiable, allowing for further feedback from the recommender system to the user. Furthermore, as we show in the rest of the paper, this measure obtains very good results, despite its simplicity.…”
Section: A Measure Of User Coherence For Recommendationmentioning
confidence: 99%
See 1 more Smart Citation
“…genres. Although other measures could be available where no external information is required, such as the entropy of the ratings [12] or the Kullback-Leibler divergence between the user's preferences and the overall preferences [4], we believe that our formulation provides a measure that is easily explainable and justifiable, allowing for further feedback from the recommender system to the user. Furthermore, as we show in the rest of the paper, this measure obtains very good results, despite its simplicity.…”
Section: A Measure Of User Coherence For Recommendationmentioning
confidence: 99%
“…By drawing from Information Retrieval related quantities, Bellogín et al present in [3,4] a family of performance predictors for users. Correlations found between ranking-based metrics and such predictors are strong, and the authors propose to exploit them in at least two applications: dynamic neighbourhood building and dynamic ensemble recommendation, where the weights for the neigbours or the recommenders would dynamically change depending on the predicted performance of each variable.…”
Section: Related Workmentioning
confidence: 99%
“…This work may also be observed from the perspective of performance prediction in Information Retrieval [7,16] and recommendation [3], where different functions have been proposed to predict the final performance of the query (in retrieval) or the target user (in recommendation). In our case, the features we have defined are assumed to be inherent to the components of the recommender system, and thus, they measure a global property of the algorithm and its corresponding similarity metric.…”
Section: Related Workmentioning
confidence: 99%
“…In particular, under some conditions such as when positive correlation is found between the predictor and the recommender performance. Currently, we have found that our predictors are able to obtain strong (around 0.5) positive correlation with some recommenders [6]. We believe this result would allow for proposing a framework in which decisions about when and how predictors should be used for ensemble recommenders can be taken.…”
Section: Dynamic Ensemble Recommendationmentioning
confidence: 69%
“…This adaptation, however, is not straightforward, since RS rank and recommend items without an explicit user query, using other inputs instead. We explore different formulations of the user clarity under different models in [6] and [8]. Different assumptions for the random variables derive different models, all of them grounded on previous probability formulations in RS such as [15].…”
Section: Predicting Performance In Recommender Systemsmentioning
confidence: 99%